Pengaruh Financial Distress Dan Leverage Terhadap Konservatisme Akuntansi - Susi Sulastri; Yane Devi Anna (Universitas Muhammadiyah Metro, 2018)
The financial statements are a description of a company's performance. Management is given the flexibility in choosing accounting methods that will be used one of them by applying accounting conservatism. The purpose of this study is to determine the effect of financial distress and leverage on accounting conservatism. The methods used in this study are descriptive and verification methods. The population of this study is mining companies listed on the Indonesia Stock Exchange in 2012-2016.The results of this study indicate that partially financial distress have a significant on accounting conservatism and the leverage have a significant on accounting conservatism. Simultaneously shows that financial distress and the leverage have a significant on accounting conservatism.Keywords: financial distress, leverage , accounting conservatism